2011
DOI: 10.1161/atvbaha.110.212068
|View full text |Cite
|
Sign up to set email alerts
|

Increased 12/15-Lipoxygenase Enhances Cell Growth, Fibronectin Deposition, and Neointimal Formation in Response to Carotid Injury

Abstract: Objective-To determine whether increased 12/15-lipoxygenase (12/15LO) expression in vivo enhances neointimal formation in response to injury. Methods and Results-12/15LO expression in the vessel wall is increased in animal models of metabolic syndrome and diabetes mellitus. Increased expression of 12/15LO enhances cultured vascular smooth muscle cell (VSMC) proliferation, an effect mediated by the helix-loop-helix factor inhibitor of differentiation 3 (Id3). Carotid endothelial denudation was performed on apol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…In fact, bone marrow transplant studies in mice demonstrate that Id3 mediated atheroprotection is not all due to bone marrow derived cells [29]. 12/15-lipoxygenase, an important enzyme that modifies LDL in the sub-endothelial space of the atheroma, can upregulate Id3 expression in VSMCs and subsequently proliferation of VSMCs [30], [31]. Additionally, VCAM-1, an important adhesion molecule for leukocyte recruitment to the vessel wall, is upregulated in VSMCs and whole aortas isolated from Id3 −/− mice [12].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, bone marrow transplant studies in mice demonstrate that Id3 mediated atheroprotection is not all due to bone marrow derived cells [29]. 12/15-lipoxygenase, an important enzyme that modifies LDL in the sub-endothelial space of the atheroma, can upregulate Id3 expression in VSMCs and subsequently proliferation of VSMCs [30], [31]. Additionally, VCAM-1, an important adhesion molecule for leukocyte recruitment to the vessel wall, is upregulated in VSMCs and whole aortas isolated from Id3 −/− mice [12].…”
Section: Discussionmentioning
confidence: 99%
“…b , upper panel), and is also an important downstream molecule of the TGF‐β signaling pathway . In addition, Id3 has transcription corepressor activity, sequence‐specific DNA binding transcription factor activity, and it is reported to negatively regulate p21 expression, which is a potent cyclin‐dependent kinase inhibitor . Using qRT‐PCR, we further confirmed that all of the three members of the Id family ( Id1 , Id2 and Id3) were upregulated by S100A8 and S100A9 stimulation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…b ). Recent research revealed that loss of Id3 enhances activation of the p21 promoter and abrogates cell proliferation . In this study, we noticed that both S100A8 and S100A9 stimulation decreased p21 mRNA expression levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The major AA‐metabolizing enzymes cyclooxygenase 2, via production of prostaglandin E 2 acting on EP3 receptor,43 12/15 lipoxygenase, and CYP4A1/A2, most likely through generation of AA metabolites 12‐, 15‐, and 20‐hydroxyeicosatetraenoic acids, respectively, also contribute to neointimal growth 44, 45, 46, 47. Whether these enzymes and CYP1B1 act in a sequential or parallel and redundant manner is not known.…”
Section: Discussionmentioning
confidence: 99%